PLANEACIÓN ESTRATÉGICA PARA LA EMPRESA COMERCIALIZADORA Y DISTRIBUIDORA DE PRODUCTOS PARA LA CONSTRUCCIÓN “CODECA” UBICADA EN LA PARROQUIA MALACATOS, CANTÓN LOJA - Salinas Guamán, Nora Mercedes (2016)
Currently in business, the implementation of a strategic plan has become very important because of the great need to improve the development of the activities in which managers venture to succeed. On the other hand the uncertainty arising from the rapid changes in the field of economic, social, political, technological and environmental; make that managers support in effective tools such as the strategic plan. By such circumstances this thesis aims general: "Carry out a strategic plan for the marketer and distributor of products for the poor of the parish Malacatos construction", in such a way that enables the increase of their participation in the local market. The development of this work has been the specific objectives as: "A diagnosis of the current situation both external and internal of the poor company"; "Develop the SWOT matrix and the matrix Porter diamond"; and "Propose a Strategic Plan for the poor company, which allows the correct performance of the same, as expected by its members". For the achievement of the goals used different methods, techniques and instruments for collecting information which served for the preparation of the thesis. Among the methods applied have: the method of deductive e inductive; who guided us to follow a logical process in our study. As well as also used different techniques to collect information, such as direct observation, the interview with the Manager of the company and the surveys applied to 6 employees and a sample of 340 clients; who with their responses allowed to detect the internal and external problems facing the company. In the Situational diagnosis of the company discussed the external aspects of the environment and the internal aspects, in order to establish the current status of the company is. For then formulate the strengths, opportunities, weaknesses and threats, for the design of the matrix SWOT, which consented to determine the results of the strategic objectives with their respective budgets and responsible. Among the strategic objectives proposed are: "to establish the business philosophy that includes the mission, vision, principles, values and organizational structures; and so to engage them to make a proper job"; "Carry out promotional and advertising programs that allow to know the products offered by the company"; "To establish a training plan for employees of the company "Poor", in order to improve the attention to the client"; "Motivate and encourage employees, and thus performance is effective and efficient in their daily work; and "improve the display of the products (metal shelves, hangers, display cases) to make it more attractive to customers". The total budget for the implementation of these objectives amounts to $14.827,00, value that will be financed by the company in its entirety. Finally there is concerning the conclusions and recommendations that are the result of our study, which will serve as a great contribution to the company to put it into practice.